THE URGENCY OF LEGAL EDUCATION FOR STUDENTS IN THE ERA OF DIGITALIZATION: BUILDING LEGAL AWARENESS IN CYBERSPACE - Sunarjo, Sunarjo; Susianto, Susianto (EDUCATUM: Scientific Journal of Education, 2026)
The rapid development of digital technology has transformed the way students interact, learn, and participate in social life through cyberspace. The increasing use of social media, online communication platforms, and internet-based applications has heightened the risk of legal violations such as cyberbullying, disinformation, privacy breaches, and hate speech. This condition indicates that technical digital literacy alone is insufficient without being accompanied by systematic and contextual legal education. This article aims to analyze the urgency of legal education for students as a foundation for building legal awareness in the era of digitalization. The study employs a descriptive qualitative approach through a literature review of various studies and regulations related to cyber law, civic education, and digital literacy. The findings reveal that legal education needs to be integrated into the school curriculum through an interdisciplinary approach that combines pedagogical aspects, digital ethics, and an understanding of cyber regulations. Legal education should not merely function as the transfer of normative knowledge, but also as a preventive effort to shape character, digital responsibility, and a culture of legal compliance from an early age. Therefore, strengthening legal education for students becomes a crucial strategy in creating a generation that is critical, ethical, and legally aware in utilizing cyberspace wisely and responsibly.